Ecological survey of Saccharomyces cerevisiae strains from vineyards in the Vinho Verde Region of Portugal - Schuller, Dorit Elisabeth (2005)
One thousand six hundred and twenty yeast isolates were obtained from 54 spontaneous fermentations performed from grapes collected in 18 sampling sites of three vineyards (Vinho Verde Wine Region in northwest Portugal) during the 2001-2003 harvest seasons. All isolates were analyzed by mitochondrial DNA restriction fragment length polymorphism (mtDNA RFLP) and a pattern profile was verified for each isolate, resulting in a total of 297 different profiles, all revealed to belong to the species Saccharomyces cerevisiae. The strains corresponding to seventeen profiles showed a wider temporal and geographical distribution, being characterized by a generalized pattern of sporadic presence, absence and reappearance. One strain (ACP10) showed a more regional distribution with a perennial behavior. In different fermentations ACP10 was either dominant or not, showing that the final outcome of fermentation was dependent on the specific composition of the yeast community in the must. Few of the grape samples collected before harvest initiated a spontaneous fermentation, compared to the samples collected after harvest, in a time frame of about 2 weeks. The associated strains were also much more diversified: 267 patterns among 1260 isolates compared to 30 patterns among 360 isolates in the post- and pre-harvest samples respectively. Fermenting yeast populations have never been characterized before in this region and the present work reports the presence of commercial yeast strains used by the wineries. The present study aims at the development of strategies for the preservation of biodiversity and genetic resources as a basis for further strain development.